Calculation of the dayside reconnection rate from cusp ion-energy dispersion - da Silva, D. E.; Chen, L. J.; Fuselier, S. A.; Trattner, K. J.; Burkholder, B. L.; DesJardin, Ian M.; Buzulukova, N.; Dorelli, J. C. (Frontiers in Astronomy and Space Sciences, 2025)
Magnetic reconnection is a fundamental process in the solar wind-magnetosphere system, driving energy transfer into the magnetosphere and space weather effects. In this study, we use the formula derived in Lockwood et al. (Journal of Geophysical Research: Space Physics, 1992, 97, 14841–14847) to calculate the dayside magnetopause reconnection rate using ion-energy dispersion data from the most modern iteration of the Defense Meteorological Satellite Program (DMSP) and modeling of the dayside southward reconnection system. We study the March 23–24, 2023, geomagnetic storm, where continuous reconnection produced seven consecutive passes of ion-energy dispersion with the DMSP F18 satellite. Our results indicated that in each case, when it is assumed that the dispersion is a temporal (rather than a spatial) structure, the reconnection rates are generally between 0.1 and 2 mV/m, commensurate with other studies. Major uncertainties arise from determining the ion cutoff energy, spacecraft trajectory angle, and injection distance. We compare our methods with an alternative |E|=|v×B| baseline method, confirming that the estimates are on the correct order of magnitude. This work lays the groundwork for adaptation to TRACERS mission data. The results highlight the potential for the long-term statistical study of reconnection rates using DMSP, combined with radar measurements and upcoming discoveries around temporal versus spatial cusp structures made with TRACERS.